(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2016)
One of legal conflicts in family law in Malaysia is conversion to Islam by one spouse from a civil marriage. Such parties encounter several vital issues, including which family law system and which court has the jurisdiction to hear and decide their divorce proceedings and whether they are still subjected to civil family law in determining the application for divorce, maintenance, child custody and inheritance, or whether they are subject to Islamic law upon their conversion and their claims are to be made at the Syariah court. Those family issues that are categorised under personal law have a great impact on the unity of the society and also affects the sanctity of Islamic law in Malaysia. This article aims to discuss some of the issues surrounding the case of conversion to Islam and also suggests some solutions according to the provisions of family law in Malaysia. Keywords: marriage, conversion to Islam, jurisdiction, shariah court, family law